2004
DOI: 10.1046/j.1439-0396.2003.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary oxidized fats on the antioxidant status of erythrocytes and their susceptibility to haemolysis in rats and guinea pigs

Abstract: Three experiments were carried out with rats (experiments 1 and 2) and guinea pigs (experiment 3) to study the effect of oxidized fats, in interaction with dietary concentrations of vitamins E and C, on the antioxidant status of erythrocytes and the rate of haemolysis. In experiment 1, diets with fresh or thermoxidized fats, containing either 25 or 250 mg alpha-tocopherol equivalents/kg were used; experiment 2 included diets with fresh or thermoxidized fats, containing 25 mg alpha-tocopherol equivalents/kg; in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
4
17
0
Order By: Relevance
“…This is in accordance with previous observations concerning the hemolysis rate in guinea pigs fed either fresh or oxidized fat with increasing concentrations of vitamins E and C (Keller et al 2004). The authors suggested that higher hemolysis susceptibility was due to a deficiency of antioxidant defences.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in accordance with previous observations concerning the hemolysis rate in guinea pigs fed either fresh or oxidized fat with increasing concentrations of vitamins E and C (Keller et al 2004). The authors suggested that higher hemolysis susceptibility was due to a deficiency of antioxidant defences.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to most other studies dealing with the effects of thermoxidized fats (Corcos Benedetti et al 1987;Dibner et al 1996;Engberg et al 1996;Hochgraf et al 1997), feeding a diet containing oxidized sunflower oils did not impair growth and did not cause symptoms of toxicity, but the dietary treatment in our experiment lasted only 14 d. The results obtained were in accordance with the observations of Keller et al (2004) in rats, of Oertel (1982) in guinea pigs and chickens, and Sheehy et al (1993) in chickens fed sunflower oil, but not linseed oil. In general, growth performance traits were not affected by the supplementation with atocopheryl acetate.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, Zdunczyk et al (2000) and Keller et al (2004) reported that oxidised dietary oils lead to a reduced antioxidant status of erythrocytes and make them more susceptible to haemolysis. It is also suggested that these detrimental effects of oxidised dietary oils can be alleviated by vitamin E supplementation (Jakobsen et al, 1993;Sheehy et al, 1993;Dibner et al, 1996;Keller et al, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, the usage of oxidised oil in diets can lead to growth depression in poultry (Cabel et al, 1988;Lin et al, 1989;Sheehy et al, 1994;Dibner et al, 1996;Engberg et al, 1996;Jankowski et al, 2000) and in other animal species (Keller et al, 2004). It has been suggested that growth depression might be due to a reduction in feed intake as a result of reduced palatability and off flavour of rancid feed, or a decrease in digestibility of the oxidised oil (Wideman, 1986;Zdunczyk et al, 2000;.…”
Section: Introductionmentioning
confidence: 99%